Implikasi Sistem Kepemiluan terhadap Pembiayaan Partai Politik di Indonesia - Rofiq Rofiq (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
Every general election is always accompanied by legal products that are regulated in law. The experience of implementing general elections in Indonesia since the old order, the new order, and the reform order has always been changing. Every amendment to the Election law is always carried out prior to the implementation of the Election on the grounds of the evaluation results of the previous Election. Changes to the electoral law are also always carried out by a package of changes to the election administration law and the law on political parties. This package of changes to laws is also called the package of changes to political laws. Then how about the changes in the post-reform election law? As in the previous elections, there have been changes in laws. A fundamental change in the post-reform Election system is the Decision of the Constitutional Court (MK) number No. 22-24 / PUU-VI / 2008 regarding judicial review of Article 214 letters a, b, c, d, and e of Law 10/2008. That is, with this Constitutional Court decision, of course there has been a change in the Election system from a closed proportional system to an open list proportional system. However, without realizing it, this change has actually opened the space for candidate competition to widen. Because candidates no longer depend on the serial number but depend on the ability to get the most grassroots votes. Changes in the Election system will be followed by changes in campaign strategies and changes in campaign finance by individual candidates and political parties. As a result, the campaign strategy of distributing money towards the end of the campaign was carried out massively. This fact cannot be covered up, which has implications for party financing. Massive open wars of money politics encourage political political parties to be able to provide financial access assistance for candidates to win the competition. This is where the dynamics of campaign finance begin, which implies that campaign finance is very expensive.